Effect of pasture versus indoor feeding regimes on the yield, composition, ripening and sensory characteristics of Maasdam cheese. (25th March 2019) - Panthi, Ram R; Kelly, Alan L; Hennessy, Deirdre; O'Sullivan, Maurice G; Kilcawley, Kieran N; Mannion, David T; Fenelon, Mark A; Sheehan, Jeremiah J
Abstract : Maasdam cheese was manufactured from standardized milk derived from each of three feeding systems: grass (GRA), grass and clover pasture (CLO), and indoor feeding of total mixed ration (TMR). Pasture‐derived cheeses had significantly lower L* (whiteness) and higher b* values (yellowness) compared to TMR‐derived cheeses. Acetate levels were significantly lower in CLO and butyrate levels significantly higher in TMR compared to the other cheeses. Grass‐fed cheese had significantly higher scores for smooth texture, ivory colour and shiny appearance compared to TMR. The influence of feed type was minimal on cheese yield, composition and on glycolysis, lipolysis and proteolysis during ripening.